Yield of Cassava Leaves (Manihot Esculenta Crantz Var Obama II) in Relation to Some Harvesting Modalities During the Crop Cycle in the Hinterland of Kisangani (Tshopo Province, R.D. Congo) - Fiston, Chebele Basila; Médard, Molongo Mokondande; Faustin, Ngama Boloy; Liston, Ofeka Kelekele; Joseph, Litucha Bakokola (Budapest International Research and Critics University, 2024)
The study examined the impact of three cassava leaf harvesting methods on the growth and leaf yield of the Obama II variety in Kisangani. The three methods were light picking (CL), moderate picking (CM) and coarse picking (CG). Results showed that plant diameter was not affected by harvesting method, but plant height and number of tender shoots were. Rough harvesting produced the tallest plants with the most tender shoots. Yields of fresh cassava leaves varied according to harvesting method, ranging from 5.36 to 12.27 t/ha, with rough picking giving the highest yield. However, light picking had the highest rates of leaf removal (63.8%) and wilting (55.4%), followed by moderate picking (CM: 49.6% rate of leaf removal and 39.0% of wilting), while coarse picking had the lowest rates of leaf removal (21.6%) and wilting (18.6%).